Obstetrical analgesia: with special reference to the ether-oil-quinine method of rectal instillation - Candlish, William John (The University of Edinburgh, 1934)
A series of twenty five maternity cases treated with rectal -ether -oil -quinine in labour is reviewed and discussed in tib light of modern practice.

Great relief was experienced in 76% of all cases and moderate relief in 20% with one failure.

No maternal deaths occurred in spite of the large percentage of abnormal cases and no foetal deaths could be attributed to its use.

Its suitability to dystocia, tuberculosis, toxaemia and induction is proved.

Labour is not unduly prolonged; it may be hastened but with careful technique rarely ceases.

Certain minor objections can be obviated by improved technique and wider experience; they are not in themselves, sufficiently serious to disqualify the method.

It is best used in hospital where skilled supervision and attention are available, but, in a modified form can be adapted to Nursing Homes.

The physical and mental condition of the patient is improved by the knowledge of ease during delivery, thus ensuring a better convalescence.

The admitted enthusiasm of the patient is the best criterion of the success of this method.